PLANES OF ENDURANCE - van Ommen, Clifford (PINS-Psychology in Society, 2025)
In this article the notion of planes of endurance (or layered sedimentations) is developed. This is in response to attempts at mastery identified in modernist and postmodernist projects where the influence of temporality is erased either by attempting to establish unassailable universals or by introducing a radical plasticity. Focussing specifically on these themes in embodiment work, the writing of William Connolly, specifically his notions of layers and sedimentation, is utilised to provide a more nuanced reading of temporality as that which is both endurance and flux. These notions provide a matrix which allows a more complex understanding of the distinction drawn between the body and the environment and the biological and the socio-cultural.